Uma investigação de aspectos de normalização na autotradução An Invincible Memory - Camargo, Diva Cardoso de [UNESP] (My University, 2011)
This paper aims at observing the particular case of an author’s and self-translator’s style concerning normalisation features present in the self-translation. Our study has its theoretical starting point based on Baker’s proposal (1993, 1995, 1996, 2000) and Scott’s investigation in order to carry out an analysis of the use of linguistic choices involving evidence of normalization. The results point out that, while participating as a self-translator, Ubaldo Ribeiro reveals individual, distinctive and preferred stylistic options which present less lexical variation; in contrast, in the situation of participating as an author, Ubaldo Ribeiro shows stylistic choices of higher lexical diversity. Observed normalisation features reveal conscious or subconscious use of fluency strategies, making the target text easier to read. Due to his renowned sound command of the target language, the results may also suggest the challenges during the translated text re-creation process faced as a self-translator could have been greater than the challenges during the previous original text creation process faced as an author

Este estudo tem por objetivo examinar o caso particular do estilo de um autor e de um tradutor de si mesmo, com relação a características de normalização. A investigação fundamenta-se na proposta de Baker para os estudos da tradução baseados em corpus (1993, 1995, 1996, 2000) e na investigação de Scott (1998) no que concerne a evidências de normalização. Os resultados apontam que, enquanto participante como tradutor de si mesmo, Ubaldo Ribeiro revela escolhas estilísticas individuais, distintivas e preferenciais, com menor variação vocabular; em contraste, na situação de participante como autor, Ubaldo Ribeiro mostra um padrão de opções estilísticas com maior diversidade lexical. As características de normalização observadas revelam o uso, consciente ou inconsciente, de estratégias para tornar o texto traduzido mais fluente e de mais fácil compreensão para o leitor alvo. Em virtude de seu invejável conhecimento da língua inglesa, os resultados também sugerem que os desafios enfrentados como autotradutor durante o processo de recriação do texto-alvo possam ter sido maiores do que os desafios enfrentados como autor durante o processo anterior de criação do texto-fonte.
Keywords: Tradução literária; Estilo do tradutor; Estudos da Tradução Baseados em Corpus; Literatura Brasileira traduzida; Normalização; João Ubaldo Ribeiro; Literary translation; Self-translator’s style; Corpus-based translation studies; Translated contemporary Brazilian literature; Normalisation; An invincible memory